Prostate cancer cells and exosomes in acidic condition show increased carbonic anhydrase IX expression and activity - Mariantonia Logozzi; Clemente Capasso; Rossella Di Raimo; Sonia Del Prete; Davide Mizzoni; Mario Falchi; Claudiu T. Supuran; Stefano Fais (2019)
Acidity and hypoxia are crucial phenotypes of tumour microenvironment both contributing to the selection of malignant cells under a micro evolutionistic pressure. During the tumour progression, nanovesicles, called exosomes and the metalloenzyme carbonic anhydrase IX (CA IX) affect the tumour growth and proliferation. Exosomes are released into the tumour microenvironment and spilt all over the body, while CA IX is a tumour-associated protein overexpressed in many different solid tumours. In the present study, to better understand the relationships between exosomes and CA IX, it has been used an in vitro cellular model of cells cultured in different pH conditions. The results showed that the acidic microenvironment induced upregulation of both expression and activity of CA IX in cancer cells and their exosomes, together with increasing the number of released exosomes. These data strongly support the importance of CA IX as a cancer biomarker and as a valuable target of new anticancer therapies.